Transfiguration of Characteristics Medan People Slang Into Formal Vocabulary of Bahasa Indonesia - Indiani, Evi; Nasution, Fitra Maidina; Azzahra, Meutia; Nasution, Nurpadillah; Ramadani, Novita; Lubis, Bambang Nur Alamsyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aimed to describe the Transfiguration of Characteristics Medan People slang into formal vocabulary of Bahasa Indonesia. The objective of the study referred to identify the general language about language changes in Medan. This research was conducted used Descriptive qualitative method. The data of this study was a result of observation and interview, and the source of the data was taken from students at University Muhammadyah Sumatera Utara. The result of this research we found the differences in transfiguration in Indonesian on a daily language use of Medan people, this is influenced by culture, ethnicity, region, religion and gender. Slang language influences Indonesian itself.